Time shifts in ʿālim’s “the great serpent”: narrative fragmentation mirroring historical gentrification - Alaki, Ahlam (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study highlights the time-shattering narrative technique employed in Rajāʾ ʿĀlim’s short story “Al-Aṣalah” “[The Great Serpent],” (1994) in light of Genette’s theory in his Narrative Discourse (1972). It argues that ʿĀlim’s deviation from the linear chronological order is not merely an aesthetic convention, but a mirroring of the fragmentary world outside the text, as perceived by the Saudi Arabian writer. With the modernization and gentrification of ʿĀlim’s hometown, the holy city of Makkah, the author finds herself witnessing a time as bewildering, and as fragmentary as the narrative time employed in her short story. The methodological approach of this study is twofold. First, a narratological reading investigatesthe nonlinear relationship between “story time” and “narrative time,” pinpointing techniques of broken chronology, or time shifts, as described by Genette: duration, order, and frequency. Then, a textual analysis validates ʿĀlim’s use of each of these time-shift techniques on the narrative level to recount specific events on the story level. The findings of this study suggest the adequacy of employing this specific “shattered” narrative technique to interpret the resulting chaos outside the world of the text. Writing and reading are therefore acts of resistance: not only against narrative displacement, but figuratively speaking, against historical amnesia.